3D printed poly(hydroxybutyrate-co-hydroxyvalerate)-45S5 bioactive glass composite resorbable scaffolds suitable for bone regeneration - Araoz, Beatriz; Karakaya, Emine; Gonzalez Wusener, Ana; Detsch, Rainer; Bizzotto, Juan; Gueron, Geraldine; Boccaccini, Aldo R.; Hermida, Elida B. (Journal of Materials Research, 2021)
3D printing for tissue engineering requires biomaterials with mechanical and biological properties suitable for both tissue regeneration and the printing process. A filament made of poly(hydroxybutyrate-co-hydroxyvalerate) (PHBV) combined with 45S5 Bioglass (BG) was used to print 3D scaffolds by fused deposition modeling (FDM). Chemical treatment of BG particles with chlorotrimethylsilane (CTMS) improved the ductility of the extruded filaments and allowed excellent printability. Controlling the printing parameter infill density (I-%), from 20 to 90%, scaffolds were obtained with interconnected pores and channel sizes in the 100-800 mu m range and exhibiting tensile modulus from 0.25 to 1.36 GPa. PHBV + BG scaffolds and PHBV scaffolds coated with CTMS treated BG particles, as a model of a rough and biologically active coating, showed no cytotoxic effects, and cells preferred the scaffolds containing BG in terms of cell spreading. Mechanical and biological properties of the scaffolds were similar to those of the extracellular matrix (ECM) of trabecular bone.
CRIS-Team WoS Importer:2021-07-16